Adelaide, a literary city - Butterss, Philip, 1958- (Open Access e-Books, 2013)
"From the tentative beginnings of European settlement to today's flourishing writing scene, Adelaide has always been a literary city. Novelists, poets and playwrights have lived here; readers have pored over books, sharing them and discussing them; literary celebrities have visited and sometimes stayed; writers have encouraged each other and fought with each other. Adelaide is literary, too, in the sense of having been written about-sometimes with love, sometimes with scorn. Literature has been important not only to the city's cultural life but to its identity, to the way it has been seen and, most importantly, to the way it has seen itself. Adelaide: a literary city broadens and deepens our understanding of Adelaide as a city of creativity and culture."--Cover description